Inhibition of BRD4 attenuates transverse aortic constriction- and TGF-β-induced endothelial-mesenchymal transition and cardiac fibrosis. (February 2019) - Song, Shuai; Liu, Liang; Yu, Yi; Zhang, Rui; Li, Yigang; Cao, Wei; Xiao, Ying; Fang, Guojian; Li, Zhen; Wang, Xuelian; Wang, Qi; Zhao, Xin; et al.
Abstract: Cardiac fibrosis (CF), a process characterized by potentiated proliferation of cardiac fibroblasts and excessive secretion and deposition of extracellular matrix (ECM) from the cells, contributes strongly to the pathogenesis of a series of cardiovascular (CV) diseases, including AMI, heart failure and atrial fibrillation. Endothelial-mesenchymal transition (EndMT), one of the sources of transformed cardiac fibroblasts, has been reported as a key factor involved in CF. However, the molecular basis of EndMT has not been thoroughly elucidated to date. At the posttranscriptional level, of the three epigenetic regulators, writer and eraser are reported to be involved in EndMT, but the role of reader in the process is still unknown. In this study, we aimed to explore the role of Bromodomain-containing protein 4 (BRD4), an acetyl-lysine reader protein, in EndMT-induced CF and related mechanisms. We found that BRD4 was upregulated in endothelial cells (ECs) in the pressure-overload mouse heart and that its functional inhibitor JQ1 potently attenuated the TAC-induced CF and preserved cardiac function. In umbilical vein endothelial cells (HUVECs) and mouse aortic endothelial cells (MAECs), bothJQ1 and shRNA-mediated silencing of BRD4 blocked TGF-β-induced EC migration, EndMT and ECM synthesis and preserved the EC sprouting behavior, possibly through the downregulation of a group of transcription factors specific for EndMT (Snail, Twist and Slug), the Smads pathway and TGF-β receptor I. In the absence of TGF-β stimulation, ectopic expression of BRD4 alone could facilitate EndMT, accelerate migration and increase the synthesis of ECM. In vivo, JQ1 also attenuated TAC-induced EndMT and CF, which was consistent with JQ1's intracellular mechanisms of action. Our results showed that BRD4 plays a critical role in EndMT-induced CF and that targeting BRD4 might be a novel therapeutic option for CF.